Artworks - Szépművészeti Múzeum (2015)
[Dt.:] Das Szépművészeti Múzeum (Museum der Bildenden Künste) in Budapest ist das größte Kunstmuseum Ungarns. Es beherbergt Objekte aus dem alten Ägypten, der Antike und der europäischen Kunstgeschichte des 13. bis 21. Jahrhunderts. Die Sammlung ist in sechs Abteilungen unterteilt: Ägyptische Kunst, Antikensammlung, Gemäldegalerie Alte Meister, Sammlung Alter Skulpturen, Graphische Sammlung, Moderne Kunst. Die Objekte Sammlung sind in der Datenbank recherchierbar. - [Engl.:] The Museum of Fine Arts (Hungarian: Szépművészeti Múzeum) is a museum in Budapest, Hungary. The museum's collection is made up of international art (other than Hungarian), including all periods of European art, and comprises of more than 100,000 pieces. The Museum's collection is divided into six departments: Egyptian, Antique, Old sculpture gallery, Old painter gallery, Modern collection, Graphics collection. The works of collection can be searched in the database.